2021
DOI: 10.1108/jhti-09-2021-0264
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the role of venturesomeness in a destination consumer-based brand equity model

Abstract: PurposeGiven the lack of research on the nomological validity of tourism destination consumer-based brand equity (CBBE) constructs incorporating core, well-established constructs from the travel and tourism discipline, this research investigates the influence of venturesomeness as a moderator in a model with destination image, satisfaction, and overall CBBE as antecedents of return intentions.Design/methodology/approachThe study uses online panel data of past visitor to the sea-side destination of Corpus Chris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 99 publications
0
8
0
Order By: Relevance
“…This study directs the comprehensive DI construct discussed in the article towards construct validity, i.e. assessing the accuracy of translating theory into actual measures (Cruz-Milán, 2021). Future research, following the development of a suitable methodology should also address its construct validity.…”
Section: Discussionmentioning
confidence: 99%
“…This study directs the comprehensive DI construct discussed in the article towards construct validity, i.e. assessing the accuracy of translating theory into actual measures (Cruz-Milán, 2021). Future research, following the development of a suitable methodology should also address its construct validity.…”
Section: Discussionmentioning
confidence: 99%
“…Tavitiyaman and Qu (2013) showed that destination image dimensions such as quality of hotels and restaurants and attractions in Thailand triggered travelers' overall satisfaction. Similarly, Cruz-Milàn (2021) found that destination's perceived image (natural environment, services and amenities) positively affected destination satisfaction. Zhang et al 's (2014) meta-analytic study showed that overall image, when compared with the affective-cognitive joint images, exerted the highest effect on tourist loyalty.…”
Section: Theoretical Backgroundmentioning
confidence: 92%
“…The economic impact of the pandemic has been severe, and it will take some time before we can return to the size and scale of pre-Covid events. Planning for the near future remains uncertain (Cruz-Mil an, 2023). While much has changed in the 20 years since Tourism Studies began, festivals have proven to be resilient and will likely re-emerge in the future, perhaps not unscathed, but with renewed purpose (Duffy and Mair, 2021).…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Revisit intention is a result of positive experiences during a tourist's visit (Han and Kim, 2010). Satisfied tourists tend to hold positive attitudes towards a destination and are more likely to return to it (Huang and Hsu, 2009; Mat Som et al , 2012; Cruz-Milán, 2023). Research in the tourism industry has shown that tourist satisfaction is a strong predictor of a person's intention to revisit and recommend a destination to others.…”
Section: Literature Reviewmentioning
confidence: 99%